Evaluasi Program Penguatan Pendidikan Karakter Terintegrasi Mata Pelajaran Matematika di SMP Negeri - Elsy Senides Hana Taunu; Ade Iriani (Universitas Kristen Satya Wacana, 2019)
This study aims to determine the implementation, influence, and factors affecting the implementation of the program in SMP Negeri 2 Waingapu. This research type is evaluative research by using a qualitative method. The evaluation program model used is a goal-free evaluation model. Interviews, observations, and document studies are techniques used for data collection. Data validity test is done with triangulation, technique and data source triangulation. The results showed that 1) the implementation of character education program in SMP Negeri 2 Waingapu has not been optimal yet, either in terms of planning, implementation or evaluation; 2) the effect of the program on integrating character values in Mathematics is positive on student achievement and behavior but also negative on teacher workload; 3) factors which affect the program are: facilities and infrastructures, information access, teachers, students.